Effectiveness of a Dental Pop-Up Book in Sign Language on the Oral Hygiene Levels of Deaf Students at Special School in Jember - Firmansyah Adi Pradana; Berlian Prihatiningrum; Roedy Budirahardjo (Knowledge Dynamics, 2025)
Background: Dental and oral hygiene is the most important issue in a child with special needs, one of which is deafness with poor hearing function. Such limitations affect knowledge, resulting in attitudes and actions in keeping their teeth and mouth clean. Education through dental and oral health uses a printing medium that uses the visual aids of the deaf. A dental pop-up sign-language book taps into a three-dimensional visual display and a mix of sign language as a medium. This study aims to determine and examine the effectiveness of a sign-language dental pop-up book on dental and oral hygiene in SDLB 1 Patrang (special school) and SDLB B Bintoro (special school). Methods: This was a type of experimental research with a pre-experimental approach. The method used was a one-group pretest-posttest with a one-week intervention. Research subjects included 25 special school students from 1 Patrang and special school B Bintoro. Results: After administering ANOVA analysis, there was a difference. The intervention given using the dental pop-up book showed a different effect. According to analysis from Bonferroni, the use of dental pop-up books is effective for deaf children in the extremely severe category. Conclusion: Dental pop-up sign-language books are effective in increasing dental and oral hygiene in special school 1 Patrang and B Bintoro.